THE RELATIONSHIP BETWEEN KNOWLEDGE, ATTITUDES, AND EXPERIENCES AND THE INCIDENCE OF VIOLENCE AMONG ADOLESCENTS IN WEST SUMATRA PROVINCE - Putri, Anggela Pradiva; Yenti, Melisa; Nasution, Suci Maisyarah (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Background: Violence directed at children refers to deliberate actions that cause physical or psychological harm, including neglecting their basic needs or inflicting physical harm. Increased cases of violence against women and children from 2019 to 2021. The number of reported cases of violence against children was recorded to have increased from 11,057 in 2019, 11,278 cases in 2020, and to 14,517 cases in 2021. The group that experienced violence based on education was at the elementary level , junior high and high school which are teenagers. In general, the factors that cause domestic violence can be classified into two factors, namely external factors and internal factors. This study was aimed at examining the relationship of knowledge, attitudes and experiences to the incidence of violence in adolescents in West Sumatra Province. Methods: This research adopts a quantitative approach using a cross-sectional design. As a sampling method, this study used purposive sampling for a total of 109 respondents using a questionnaire measuring instrument distributed using google form. Analysis of the data used in this study with univariate analysis and bivariate analysis using chi-square. Results: The results of the analysis show that some respondents have experienced violence, have a high level of knowledge, have a positive attitude, and have never experienced violence. The results of the bivariate analysis showed that there was a relationship between attitudes and the incidence of violence with p-value = 0.001 and experience with violent incidents with p-value = 0.000. Conclusion: There is a relationship between attitudes and experiences towards the incidence of violence against adolescents in West Sumatra Province in 2022.